2013
DOI: 10.1177/0363546513501508
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Posterior Shoulder Instability in Young Athletes

Abstract: This is the largest known prospective study to follow healthy participants in the development of posterior shoulder instability. Posterior instability represents 10% of all instability events. The most significant risk factor was increased glenoid retroversion. While increased internal/external strength was also associated with subsequent instability, it is unclear whether these strength differences are causative or reactive to the difference in glenoid anatomy. This work confirms that increased glenoid retrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
139
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 22 publications
3
139
3
1
Order By: Relevance
“…The role of imaging in predicting shoulder instability has been explored to a degree in the literature. Owens et al 11,12 demonstrated a correlation with anatomic variation in shoulder girdle anatomy, specifically related to glenoid version and shape and coracohumeral distance. As many patients in our study did not have 3-dimensional imaging available for review at the time of data collection, analysis of these particular data points was not possible; however, future studies could examine these features in patients who go on to shoulder instability surgery to determine whether there is an association between certain imaging findings and need for operative intervention and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of imaging in predicting shoulder instability has been explored to a degree in the literature. Owens et al 11,12 demonstrated a correlation with anatomic variation in shoulder girdle anatomy, specifically related to glenoid version and shape and coracohumeral distance. As many patients in our study did not have 3-dimensional imaging available for review at the time of data collection, analysis of these particular data points was not possible; however, future studies could examine these features in patients who go on to shoulder instability surgery to determine whether there is an association between certain imaging findings and need for operative intervention and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Owens et al 2 prospectively studied 714 young athletes from 2006-2010. Patients underwent stability testing, strength testing, and bilateral noncontrast MRI scans.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because anterior instability and multidirectional instability (MDI) are more common, most of the available literature pertains to these entities. Nevertheless, studies have begun to investigate the risk factors, outcomes, and surgical treatments associated with posterior instability.…”
mentioning
confidence: 99%
“…1,2,3 It is also increasingly seen in non-athletic groups such as those of older age and in certain unique groups such as wheelchair users. 4,5 Compared to anterior shoulder instability, posterior instability is relatively rare, with the incidence described to be around 2-10%.…”
Section: Introductionmentioning
confidence: 99%